Trace Elements and Their Effects on Human Health and Diseases 2021
DOI: 10.5772/intechopen.95491
|View full text |Cite
|
Sign up to set email alerts
|

Role of Trace Elements in Breast Cancer and Their Characterization Using X-Ray Fluorescence Techniques

Abstract: Breast cancer is the most common serious disease that occurs in the human body. Trace elements have an important function in biological and metabolism processes including activation or inhibition of enzymatic reaction, reactive oxygen species (ROS), competition between trace elements and metal proteins for binding positions and modifications in the permeability of cellular membranes which influence carcinogenic processes. A significant association between the abnormal concentration of trace elements and breast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 75 publications
(108 reference statements)
0
2
0
Order By: Relevance
“…Many scientific and therapeutic efforts are underway to identify and combat cancer effectively. For this purpose, some X-ray-based imaging techniques like particle-induced X-ray emission (PIXE), energy-dispersive X-ray spectroscopy (EDX), and X-ray fluorescence microscopy (XRF) were used [3][4][5]. Still, these techniques have low sensitivity and accuracy [6].…”
Section: Introductionmentioning
confidence: 99%
“…Many scientific and therapeutic efforts are underway to identify and combat cancer effectively. For this purpose, some X-ray-based imaging techniques like particle-induced X-ray emission (PIXE), energy-dispersive X-ray spectroscopy (EDX), and X-ray fluorescence microscopy (XRF) were used [3][4][5]. Still, these techniques have low sensitivity and accuracy [6].…”
Section: Introductionmentioning
confidence: 99%
“…Trace elements are essential for the activity of numerous enzymes, and therefore, variations in the serum levels of these biochemical markers may be linked to the pathogenesis of various cancers, including oral cancer (17). Therefore, the role of trace elements has been extensively studied in recent years in various types of cancer, such as breast (18)(19)(20), gastric (21,22), lung (23)(24)(25), oral (17,(26)(27)(28)(29) and pancreatic cancers (30), as well as in liver cirrhosis (30). A number of studies have concluded that trace elements can be used for the early prediction or diagnosis of cancer (17,18,23,(26)(27)(28)(29).…”
Section: Comparative Analysis Of Trace Elements In the Saliva And Ser...mentioning
confidence: 99%